1998
DOI: 10.1038/23948
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory agents aspirin and salicylate inhibit the activity of IκB kinase-β

Abstract: NF-kappaB comprises a family of cellular transcription factors that are involved in the inducible expression of a variety of cellular genes that regulate the inflammatory response. NF-kappaB is sequestered in the cytoplasm by inhibitory proteins, I(kappa)B, which are phosphorylated by a cellular kinase complex known as IKK. IKK is made up of two kinases, IKK-alpha and IKK-beta, which phosphorylate I(kappa)B, leading to its degradation and translocation of NF-kappaB to the nucleus. IKK kinase activity is stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
1,017
9
17

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,502 publications
(1,073 citation statements)
references
References 25 publications
30
1,017
9
17
Order By: Relevance
“…Initial observations indicate that ASA prevented the phosphorylation and degradation of I B␣, causing cytoplasmic trapping of NF-B (19,20). Yin et al (33) have recently reported that the inhibitory effect of ASA resulted from the specific inhibition of ATP binding to I K␤. As a consequence, phosphorylation of I B␣ was markedly reduced, which prevented its degradation and activation of the NF-B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Initial observations indicate that ASA prevented the phosphorylation and degradation of I B␣, causing cytoplasmic trapping of NF-B (19,20). Yin et al (33) have recently reported that the inhibitory effect of ASA resulted from the specific inhibition of ATP binding to I K␤. As a consequence, phosphorylation of I B␣ was markedly reduced, which prevented its degradation and activation of the NF-B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…While they are somewhat effective in achieving glucose control at high doses, side effects, such as gastrointestinal bleeding and tinnitus, prevent their widespread use [28]. These compounds are relatively weak inhibitors of Ikkb, thus preventing Irs1 serine307 phosphorylation and this presumably accounts for their insulin-sensitizing effects [29]. Several approaches have been used to demonstrate IkkbÕs direct involvement in diet-induced chronic inflammation and insulin action.…”
Section: Ikkbmentioning
confidence: 99%
“…Aspirin is commonly thought to act pharmacologically primarily via inhibition of prostaglandin synthesis (Weissmann, 1991). However, at higher concentrations, aspirin has also been shown to block NF-kB activity by directly binding to and inhibiting the kinase activity of IKKb by reducing its ability to bind ATP (Yin et al, 1998); more recently, aspirin has also been reported to inhibit proteasome activity and consequently to interfere with degradation of IkB (Dikshit et al, 2006). As such, high-dose aspirin therapy may have applications to diseases where NF-kB activity is involved, including cancer (McCarty and Block, 2006), diabetes (Yuan et al, 2001) and heart disease (Li and Fang, 2004).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%